Economic Efficiency of Intensive Care Units Department of Hospitals Affiliated With Yazd University of Medical Sciences: A DEA Approach - Mahdieh Abedi; Mohammad amin Bahrami; Hasan Yusefzade; Mohammad Mehdi Kiyani; Maryam Moeini (Kerman University of Medical Sciences, 2016)
Introduction:Hospitals as the most expensive health care system is an operational unit, considering the cost efficiency of this unit is very important. The aim of this study was to evaluate the performance of the intensive care units of hospitals affiliated with Yazd University of Medical Sciences. Methods:This is a descriptive - analytic study performed in 2014. Intensive care units of 8 hospitals affiliated with Yazd University of Medical Sciences were included in this study. Data envelopment analysis (DEA) was used to evaluate the economic efficiency of intensive care units. Input variables included the number of physicians, nurses, and active beds, as well as the number of equipment (ventilator), and output variables included bed occupancy rate and the number of patients discharged healthy. Input prices contained the doctors and nurses income, bed price, and depreciation cost of equipment (ventilator). Results:The findings show that among 8 studied hospitals, the efficiency of 5 hospitals were 1 and the efficiencies of the other hospitals were 0.174, 0.645, and 0.855. The mean economic efficiency of intensive care units of all hospitals was 834.0 in 2014. Conclusion:By ameliorating the allocation of resources allocated for hospitals including human resources and equipment, the efficiency level of hospitals can be improved. Keywords:Economic Efficiency, Educational Hospital, Data Envelope Analysis (DEA). Citation: Abedi M, Bahrami MA, Yusefzadeh H, Kiani MM, Moeeni M.Economic Efficiency of Intensive Care Units Department of Hospitals Affiliated With Yazd University of Medical Sciences: A DEA Approach.Journal of Health Based Research 2016; 2(1): 29-38. Fax: 03136684799 Email: m.moeini1387@gmail.com